Medical work in Bac Ninh province while the hypothetical situation of a cross-border radiation accident - Nguyen, Tien Quan; Nguyen, Thi Minh; Bui, Van Loat; Le, Ngoc Thiem (Tạp chí Y Dược Huế, 2024)
Introduction: The hypothetical situation of a cross-border radiation accident comes from a hypothetical accident at the Fanchenggang nuclear power plant, which could affect Bac Ninh province. Therefore, the Bac Ninh Provincial Department of Health must develop a medical response plan. In response to these challenges, this study assesses the absorbed dose during the hypothetical situation of a cross-border radiation accident and an appropriate medical response plan in Bac Ninh. Materials and methods: This study mentions the characteristics of reactor accident scenario. It used interpolation methods to evaluate the radiation dose in the event of a nuclear accident. In addition, the study presents the human resources infrastructure of the health sector to implement the response. Results: In the worst-case scenario, adults may be exposed to a maximum absorbed dose of about 1.4 mSv per day. If the projected dose exceeds the generic criteria of 100 mSv/year, the Bac Ninh Health Sector will take protective actions and provide medical response. Conclusion: In areas affected by nuclear power plants, it is mandatory to respond to radiation accidents